Culture-bearing Women The Black Women Renaissance and Cultural Nationalism - Penier, Izabella (De Gruyter, 2019)
The study examines the fiction of Black Women's Renaissance. It focuses on the novels of the 1980s, which appreciated "culture-bearing" mothers as reproducers of the nation, to analyze the vexed relationship between cultural nationalism and feminism. It argues that the BWR created "matrifocal" nationalism that made black women principal agents of national identity, but also promoted gender essentialism at the expense of social and economic issues.